On species related to Elachista hedemanni Rebel (Lepidoptera: Elachistidae: Elachistinae), with descriptions of three new Palearctic species - Kaila, Lauri (Zootaxa, 2012)
The taxonomy of Elachista (Aphelosetia) hedemanni Rebel, 1899, and its relatives is clarified. The following species aredescribed as new: Elachista gilvula sp. n. from Russia: Tuva with additional record from Kazakhstan, Elachista galbinasp. n. from Kazakhstan and Elachista cirrhoplica sp. n. from Spain. The systematics of an assemblage of species relatedto Elachista (Aphelosetia) pollinariella Zeller is discussed, and characters possibly enabling the further division of the subgenus Aphelosetia to more manageable units are suggested.